Responding to emergencies - Rooney, Anne (Chicago, Ill Heinemann Library, 2013)
All around the world there are charities ready to respond to emergencies, from huge natural disasters like earthquakes and industrial accidents like the Fukushima nuclear plant, to civil disorder and daily accidents like capsized boats and mountain rescue
Ssience
a gift from book africa
1 2 13
Keywords: Disaster relief -- Juvenile literature; Emergency management -- Juvenile literature